Rapid and sensitive detection of Pseudomonas aeruginosa using multiple cross displacement amplification and gold nanoparticle-based lateral flow biosensor visualization. Issue 14 (19th June 2018) - Zhao, Fan; Niu, Lina; Nong, Jinqing; Wang, Chunmei; Wang, Jing; Liu, Yan; Gao, Naishu; Zhu, Xiaoxue; Wu, Lei; Hu, Shoukui
Abstract: Pseudomonas aeruginosa causes nosocomial infections of burn patients and other immunocompromised individuals, but the conventional diagnosis of P. aeruginosa infection depends on time-consuming culture-based methods. Hence, a simple, fast, sensitive technique for detection of P. aeruginosa using multiple cross displacement amplification (MCDA) and gold nanoparticle-based lateral flow biosensors (LFB) was developed. By using this technique, the reaction could be completed at an optimized constant temperature (67°C) within only 40 min. The reaction product could be detected visually using an LFB, eliminating the need for special equipment. The P. aeruginosa -MCDA-LFB method was highly specific, and accurately distinguished P. aeruginosa from other pathogens. Just 10 fg of genomic DNA template (from pure culture) could be detected. The assay could also detect P. aeruginosa in clinical sputum samples and showed the same sensitivity and specificity as the reference (culture-biochemical) method. In the future, this rapid, simple and accurate P. aeruginosa -MCDA-LFB technique might be applied in clinical practice. Abstract : Multiple cross displacement amplification with gold nanoparticles-based lateral flow biosensor could be used for detection of Pseudomonas aeruginosa, which would save much time compared with the clinical traditional method.